An Analysis Of Students Difficulties In Writing Recount Text On The Eleventh Grade At SMA Negeri 21 Medan - Sianturi, Riasty Latanya; Tampubolon, Sahlan; Napitupulu, Fenty Debora; riasty, Riasty Latanya Sianturi (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2024)
This thesis is about an analysis of students difficulties on writing recount text in the eleventh grade at SMA Negeri 21 Medan. The objectives of research are to analyze the student's difficulties on writing recount text in the eleventh grade at SMA Negeri 21 Medan And to identify the factors causing students difficulties in writing recount text. This research was conducting by applying Descriptive Qualitative research. The Researcher took 15 students of eleventh in getting the data. The instrument of the collecting data was the writing test and interview. The technique of collecting data was the researcher explained what the recount text, generic structure, language features and giving the example of recount text. The researcher asked the eleventh grade students wrote a recount text that chooses by themselves in 60 minutes and the researcher collected the paper, after that the researcher do the interview directly to all student. the result of the analysis of students difficulties showed that majority of the students at eleventh grade at SMA Negeri 21 Medan still low in writing recount text. it could be seen from the analysis the test from content of the results of the percentage is 15%, organization of the result on the percentage is 19%, language use of the percentage in the result is 26%, vocabulary of the percentage in the result is 24% and mechanic of the percentage in the result is 16%. Based on the result of analysis of student difficulties showed that majority of the students factors are difficulties of content such as the lack of experience to developing ideas. Difficulties of organization, students lack of structure to organize ideas and story elements in a clear and logical manner. Difficulties of vocabulary, the lack of word in English and limitation of vocabulary to translate the meanings of certain words. Difficulties of language use, lack of grammar such as use of sentence structure, the use of nouns, verbs, and aspects of grammar. And the last Difficulties of Mechanic, lack of knowledge about punctuation marks such as commas periods and each other formats. The analysis shows that students still make mistakes in all five aspects of the 15 students who were used as participants, none of them succeeded in writing recount correctly. so it can be concluded that students are still difficult in writing recount text.